The Mystery At The Dog Show The Boxcar Children # 35 - Gertrude Chandler Warner (U.S.A Scholastic)
At the local dog show the Boxcar children investigate when they suspect someones is trying to sabotage it.
Keywords: Mystery -- Mystery